Shame Compensation in Islamic and Psychological Perspectives - Syarnubi Syarnubi; Septia Fahiroh; Sukirman, Sukirman; Sukardi, Ismail (Tadrib: Jurnal Pendidikan Agama Islam, 2024)
This study seeks to investigate the kind of compensation obtained by individuals with shyness. The study findings clarify that compensation can be acquired either directly or indirectly, with direct compensation being further categorized into two types. Compensation, from a psychological standpoint, refers to the rewards or benefits that individuals obtain, which can directly contribute to overcoming personal challenges such as shyness and preventing various health conditions including cardiovascular illnesses, elevated blood sugar levels, and others. Furthermore, according to the Islamic viewpoint, providing compensation to a Muslim who possesses a sense of Shame will serve as a deterrent against engaging in immoral actions and transgressions. Moreover, indirect compensation refers to the rewards gained by an individual in the form of Allah's promise, namely the assurance of being granted entry into heaven and being elevated to the greatest rank. This includes being seen as devout, possessing wisdom, and being admired by numerous individuals.